DIGITAL MARKETING: CONSUMER BEHAVIOR - G. V. Butkovskaya; A. V. Statkus (Вестник университета)
Corporations direct significant funds to create a “digital relationship” with customers. The article deals with the results of research in the field of digital marketing, in particular theoretical and research issues of changes in consumer behavior under the influence of digital technologies and the digital environment. The basis for future researches of consumer behavior has been introduced, which highlights the points of contact in the implementation of the marketing strategy and tactics, where digital technologies have and will have a significant impact.